Finite element analysis of the temperature dependent conductivity of metallic hollow sphere structures - Fiedler, T.; Ochsner, Andreas (2007)

(untitled)
In the scope of this study, finite element analysis is applied in order to determine the effective thermal conductivity of periodic metallic hollow sphere structures (MHSS). Two different joining technologies for the connection of the hollow spheres, namely sintering and adhesive bonding, are considered. For the determination of the thermal conductivity of the MHSS, the temperature dependence of the thermal conductivities of the base materials, i.e. hollow spheres and joining element, are considered. Two different cases, a low and a high temperature gradient within the structure are distinguished. Furthermore, the overall thermal conductivities of sandwich panels with an insulating MHSS core in dependence on the relative face sheet thickness are investigated.